“Go Healthy”: Diet Catering for Obese Consumers with a Consumer Discovery Approach - Nadya Yona Eka Putri; Retnaningsih Retnaningsih; Asep Taryana (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2023)
The main health problem in the adult age group in Indonesia is obesity, which is closely related to diet. The purpose of this research is to design a verified business model for